Binary Oxide Superlattices: Versatile Tunability of the Metal Insulator Transition in (TiO2)m/(VO2)m Superlattices (Adv. Funct. Mater. 51/2020). (15th December 2020) - Eres, Gyula; Lee, Shinbuhm; Nichols, John; Sohn, Changhee; Ok, Jong Mok; Mazza, Alessandro R.; Liu, Chenze; Duscher, Gerd; Lee, Ho Nyung; McNally, Daniel E.; Lu, Xingye; Radovic, Milan; et al.
Abstract : The fabrication of binary oxide superlattices is undertaken as a general approach for exploring novel concepts and phenomena in reduced dimensionality systems of strongly correlated oxides. In article number 2004914, Gyula Eres, Milan Radovic, Thorsten Schmitt, and co‐workers achieve a wide range of tunability of the metal insulator transition in VO2 while reducing oxygen vacancy formation that is detrimental to electrical properties. The design was prepared by Yun‐Yi Pai and Gyula Eres both of ORNL.